Effects of Pharmaceutical Compounds in Tadpoles - dos Reis Martinez, Claudia Bueno; Aguiar, Aline [UNESP] (Taylor & Francis, 2024)
Over the past decades, the alarming rates of amphibian population decline have attracted attention to these organisms from ecotoxicological perspectives, especially using tadpoles as models. In parallel, concerning levels of contaminants such as pharmaceuticals have been found globally in many aquatic ecosystems. Although the majority of these compounds are in common use by the world population, such as analgesics and antibiotics, the medicine classes found in natural environments present wide diversity. To date, approximately 30 pharmaceutical compounds have been used in different experimental studies, with 16 species of tadpoles belonging to the families Bufonidae, Hylidae, Leptodactylidae, Pipidae, and Ranidae. According to these studies, the main pharmaceutical effects found in tadpoles are morphological abnormalities and alterations in the development, growth rates, and physiological biomarkers. Changes in behavior and cytotoxic effects were observed mainly after anthelmintic and psychiatric drug exposures, while antivirals displayed high bioaccumulation levels. Some studies showed that the mixture of pharmaceuticals had harmful effects, which possibly resulted from synergistic, antagonistic, and/or additive interactions between the mixed components; the main effects are related to physiological, metabolic, and morphological responses. All these effects could impair fitness-related traits in tadpoles, besides having a potential impact on populations and species perpetuation dynamics. Other approaches are encouraged in future research, such as the bioaccumulation potential of a given pharmaceutical and its persistency in the environment, as well the influence of intrinsic abiotic variables on the observed effects. It is also important that researchers provide precise exposure time (e.g., hours or days) and consider tadpole development in the experiments. All the collected evidence should be used by governments to establish guidelines and regulatory policies for aquatic ecosystem conservation.